Distinct Proteins in Protein Corona of Nanoparticles Represent a Promising Venue for Endogenous Targeting – Part II: In vitro and in vivo Kinetics Study - Sebak, Aya Ahmed (Int J Nanomedicine, 2020)
INTRODUCTION: Nanoparticles (NPs), upon introduction to the biological systems, become wrapped by serum and cellular proteins constituting the protein corona (PC). This PC contributes largely to the NPs’ interaction with the biological systems and their subsequent functions. On the one hand, PC can decrease the efficiency of targeting by directing the NPs to the reticuloendothelial system (RES) or by masking the active targeting moieties and decreasing their ability to bind to their target receptors. On the other hand, some components of PC have offered hopes for achieving endogenous targeting. METHODS: In this study, we aimed at the investigation of the role of the PC in determining the behavior of cRGDyk peptide-unconjugated and -conjugated NPs (uNPs and cNPs) exhibiting different physicochemical properties and their interaction with melanoma on in vitro and in vivo levels. Mathematical modeling has been utilized to understand the kinetics of the interaction of NPs with the tumor cells and different organs, respectively. RESULTS: Endocytosis and exocytosis were reported to occur simultaneously for the utilized NPs. The balance was largely dependent on the NPs’ physicochemical properties and the role of the PC. In addition, distinct proteins present in the PC (illustrated in the results of the PC analysis in part I) have also determined the patterns of the NPs’ distribution in different organs and tissues of the vascular system, the RES system and the target tumot tissue. Vitronectin (VN) was found to mediate higher accumulation in integrin receptor-expressing melanoma cells, while complement 3 protein (C3) and clusterin (CLU), as an opsonin and dysopsonin, respectively, regulated the balance between the RES uptake and blood circulation. DISCUSSION: PC, if properly modulated by tuning NPs’ physicochemical properties, can serve as a potential venue for optimum utilization of NPs in cancer therapy.